Sustainability Status of Residential Areas in Bumi Harapan Village, Nusantara Capital City: A Multi-Dimensional Scaling (MDS-RAPSettlement) Approach - Oza Satria; Ernan Rustiadi; Sugeng Budiharsono (Politeknik Siber Cerdika Internasional, 2026)
Background: The development of the Nusantara Capital City (IKN) as a sustainable forest city raises concerns regarding the sustainability of rural settlement areas that have long existed within its boundaries. Objective: This study aims to assess the sustainability status of the Bumi Harapan Village settlement across ecology and infrastructure, economic, socio-cultural, and institutional dimensions and to identify sensitive attributes that may inform sustainable settlement development. Methods: The study was conducted in Bumi Harapan Village using field observations, a questionnaire administered to the village government, and secondary data. Sustainability was assessed using Multi-Dimensional Scaling (MDS)-RAPSettlement across 39 attributes grouped into four dimensions. Results: Bumi Harapan is moderately sustainable in the ecology and infrastructure dimension (60.05) and institutional dimension (62.58), but less sustainable in the economic dimension (41.16) and socio-cultural dimension (41.89). RSQ values range from 0.94 to 0.95 and stress values from 0.133 to 0.137. The most sensitive attributes include waste management, green open space, clean water availability, village market availability, community participation in waste management, and participation in decision-making. Conclusion: These findings support evidence-based efforts to improve the sustainability of the Bumi Harapan settlement, particularly by strengthening environmental services, local economic capacity, community participation, and responsive village governance.